CYCLIC BENDING OF VARIOUS GLASS FIBRES REINFORCED WITH POLYMER COMPOSITE ARCHITECTURES - Pop, Mihai Alin; Geamqn, Virgil; Motoc, Dana Luca; Monescu, Vlad; Radomir, Irinel (European Scientific Journal, ESJ, 2014)
The paper presents a contribution to the study and characterization of special composite materials based on resins reinforced with glass fiber and wire netting. Several tests were made previously for testing the behavior of the composites with resin reinforced with glass fiber to determine the physical and mechanical properties. There were used the following materials: Nestrapol 96 type resin reinforced with wire net with the specific weight of 400 [g/m2] and a number of 3, 5 and 7 layers, Stratimat type fiber glass with the specific weight of 300, 450 and 600 [g/m2] and a number of 3, 5 and 7 layers and a Tissue type fiber glass with the specific weight of 300 and 500 [g/m2]. The results obtained for those composites were compared with the results obtained for resin Nestrapol 96 without reinforcement. The second aim of this paper, was to make a mathematical modeling and an optimization of the resin type of composite materials reinforced with wire net and two types of fiber glasses. The modeling and optimization of these composites are based on the results obtained previously from the bending test and cyclical bending test.